The immunophenotype of mast cells and its utility in the diagnostic work-up of systemic mastocytosis. Issue 1 (7th November 2014) - Teodosio, Cristina; Mayado, Andrea; Sa´nchez-Mun oz, Laura; Morgado, Jose´ M; Jara-Acevedo, Mari´a; A´lvarez-Twose, Ivan; Garci´a-Montero, Andre´s C; Matito, Almudena; Caldas, Caldas; Escribano, Luis; Orfao, Alberto
Abstract : Review of normal/reactive mast cell maturational profiles for the identification of aberrant phenotypes used in the diagnostic work-up of systemic mastocytosis. Abstract: SM comprises a heterogeneous group of disorders, characterized by an abnormal accumulation of clonal MCs in 1 or more tissues, frequently involving the skin and BM. Despite the fact that most adult patients (>90%) carry the same genetic lesion (D816V KIT mutation), the disease presents with multiple variants with very distinct clinical and biologic features, a diverse prognosis, and different therapeutic requirements. Recent advances in the standardization of the study of BM MC by MFC allowed reproducible identification and characterization of normal/reactive MCs and their precursors, as well as the establishment of the normal MC maturational profiles. Analysis of large groups of patients versus normal/reactive samples has highlighted the existence of aberrant MC phenotypes in SM, which are essential for the diagnosis of the disease. In turn, 3 clearly distinct and altered maturation-associated immunophenotypic profiles have been reported recently in SM, which provide criteria for the distinction between ISM patients with MC-restricted and multilineage KIT mutation; thus, immunphenotyping also contributes to prognostic stratification of ISM, particularly when analysis of the KIT mutation on highly purified BM cells is not routinely available in the diagnostic work-up of the disease.